RETINAL DETACHMENT SURGERY IN A PEDIATRIC POPULATION: Visual and Anatomic Outcomes. Issue 7 (July 2018) - Read, Sarah P.; Aziz, Hassan A.; Kuriyan, Ajay; Kothari, Nikisha; Davis, Janet L.; Smiddy, William E.; Flynn, Harry W.; Murray, Timothy G.; Berrocal, Audina
Abstract : Purpose: Pediatric retinal detachments (RDs) are unique in etiology, anatomy, and prognosis compared with the adult population. The mechanisms of pediatric RD include tractional (TRD), rhegmatogenous retinal detachment, traumatic, and other types, such as exudative or hemorrhagic. This study examined visual and anatomical outcomes of pediatric RD undergoing surgical repair at a single university referral center. Methods: A retrospective consecutive case series of patients clinically diagnosed and undergoing surgery for RD between birth and 15 years of age from 2002 to 2013 at a single academic institution. Results: A total of 206 patients (231 eyes) were included in this study, of which 25 (12%) had bilateral RD. Of those patients, 67 (29%) had TRD (retinopathy of prematurity, persistent fetal vasculature, or familial exudative vitreoretinopathy), 51 (22%) had rhegmatogenous retinal detachment (myopia, X-linked retinoschisis, or Stickler syndrome), 60 (26%) had traumatic RD, and 53 (23%) were due to other types of RD, such as Coats disease or coloboma. Presenting best-corrected visual acuity better than 20/200 correlated with better final best-corrected visual acuity ( P < 0.0001). Anatomical success was strongly correlated with visual acuity outcome ( P < 0.00001) and was significantly more likely in rhegmatogenous retinal detachment versus TRD (78% vs. 39%, P < 0.05). The rates of obtaining a final best-corrected visual acuity > 20/200 were poorer in TRD (10%) compared with rhegmatogenous retinal detachment (39%, P < 0.01) or traumatic RD (28%, P < 0.05). Conclusion: Visual and anatomical outcomes varied among categories of RD. Rhegmatogenous retinal detachments were associated with the best outcomes (anatomical success and globe conservation), whereas TRDs generally had poorer visual and anatomical outcomes. Abstract : Supplemental Digital Content is Available in the Text.The current study is one of the largest to examine the surgical intervention and outcomes of pediatric traumatic, rhegmatogenous, and tractional detachments. Overall, outcomes were best in rhegmatogenous and worst in tractional detachments.